Characterization of an unusual adenovirus strain, Sibu 97 - Perera, David (Universiti Malaysia Sarawak, (UNIMAS), 2005)
n adenovirus isolate, SIBU97, associated with an unexplained cluster of deaths of children with fatal acute myocardial dysfunction in Sarawak was characterized and compared with other human adenoviruses. The research is study the sequence comparisons with GenBank of portions of the SIBU97 genome that include the E1, E2, and E3 transcript regions showed that it shared >94% identity to human species B adenoviruses and simian adenovirus type 21. A comparison of restriction digest profiles of SIBU97 with prototype species B adenoviruses and several European Ad21 variants revealed profiles generated with Bam H1, Sma ! and Kpn 1 that differed from the other adenoviruses but were closely related to prototype Ad21.